AB1163 Antibodies binding synthetic oligonucleotides distinguish lupus from rheumatoid arthritis, scleroderma and sjogren's syndrome. (15th June 2017) - Putterman, C; Gabrielli, A; Balbir-Gurman, A; Safer, P; Jakobi-Brook, K; Sorek, R; Gluzman, I; Wallace, S; Cohen, IR
Abstract : Background: The SLE-key® RuleOut iCHIP® antigen microarray-based test rules out a diagnosis of SLE with a sensitivity of 94% 1 . Objectives: Here we report the use of the iCHIP® platform and a set of synthetic oligonucleotide antigens to distinguish between SLE subjects and those with a diagnosis of Rheumatoid Arthritis (RA), Scleroderma (SSc), Sjogren's syndrome (SS), or healthy individuals (HC). Methods: We examined IgM and IgG antibody binding to 22 synthetic oligonucleotides (44 features) in the sera of HC subjects (N=40); SLE (N=30); SSc (N=40); SS (N=20); or RA (N=30) patients. Univariate analysis (FDR adjusted p-values) was used to determine the ability of each feature to separate between SLE and the different classes of subjects. Results: Table 1 shows that multiple oligonucleotides successfully distinguished SLE patients from all other groups. All significant features were IgG antibodies, except for 1 IgM. Table 2 shows the impact of single nucleotide change on autoantibody binding. PolyG (G17) separates SLE from all but SS. T1G16 separates SLE from HC subjects, while G16T1 gave no significant separation. The addition of a G to the 5' and 3' end of T16 enhanced IgG antibody binding and improved separation between SLE and other autoimmune diseases with at least 10-fold improved significance as compared to T20. PolyG sequence length impacts the ability of the oligonucleotides to separate between SLE and the other groups (Fig. 1 A). Unexpectedly, sequences either shorter or longer than G14 were effective in separating SLE from HC, RA, and SSc, while G14 was not effective. Furthermore, none of the polyG homopolymers could separate SLE from SS. Sequences rich in C or T were more effective at separating between SLE and SS patients (Fig. 1 B). Conclusions: Autoantibody binding to oligonucleotides can be used to differentiate SLE from other autoimmune conditions and healthy subjects. The structural basis for the differences in binding of antibodies from disease sera to the various oligonucleotides is not yet understood, but may be due to immunologically unique conformations and secondary structures of oligonucleotides of defined length and sequence. SSc can be differentiated from SLE based on particular antibody binding to epitopes of oligonucleotides containing C and T. RA can be differentiated from SLE more significantly than the other autoimmune conditions. The iCHIP® microarray technology is being further developed to generate a clinically useful test to rule in a diagnosis of SLE relative to other related autoimmune diseases. References: Putterman et al., J Immunol Methods 2016. Fattal et al., Immunology, 2010. Fattal et al., Immunology, 2015. Acknowledgements: Authors wish to acknowledge Cohen-Gindi O, Lerner M, Tarnapolski O, Blumenstein Y, Javaherian A, Pitts J, Barton M and Wong E. and the Innovative Medicines Initiative Joint Undertaking under grant agreement n° 115308 BIOVACSAFE. Disclosure of Interest: C. Putterman Consultant for: ImmunArray, A. Gabrielli: None declared, A. Balbir-Gurman: None declared, P. Safer Employee of: ImmunArray, K. Jakobi-Brook: None declared, R. Sorek Employee of: ImmunArray, I. Gluzman Employee of: ImmunArray, S. Wallace Employee of: ImmunArray, I. Cohen Shareholder of: ImmunArray, Consultant for: ImmunArray